The Simplest Memristor Circuit With Hyperchaos - Liu, Xingce; Wang, Jinpeng (Frontiers in Physics, 2022)
In recent years, with the in-depth study of memristor, meminductor and memcapacitor, the fourth basic element has been developed vigorously. The chaotic circuit including meminductor, memcapacitor and memristor is designed in this paper. Equation of state for the chaotic system is obtained according to Kirchhoff's volt-current law, and the mathematical model of the chaotic system is obtained through dimensionless processing. And, the stability of equilibrium point is analyzed in detail and the dynamical behaviors of the system are analyzed by the traditional method such as LEs and Bifurcation diagram. Besides, some special phenomena exist in the system, such as state transition and coexistence of attractors. Finally, the circuit is implemented by DSP to prove the realizability of chaotic circuit.